Factors affecting Bologna process course registration in Architectural Engineering Department-Salahaddin University - Salahaddin Yasin Baper (Zanco Journal of Pure and Applied Sciences, 2024)
Developing the traditional higher educational system towards bologna process is considered as the instruction for reshaping in the higher education system in Kurdistan. This transformation faced crucial difficulties in term of course selection in Kurdistan universities. This study aims to explore thoughts, obstacles and difficulties that face students in term of course selection. Further, it tries to formulate an equation of operative factors that affection course selection in bologna process system. The rationale behind applying bologna process in Kurdistan is related to create common higher education area which intended to increase mobility, and inclusive comparability of programs within similar higher education institutes in the region. More precisely, the intention is to indicate how bologna process course selection have affected what goes on in the classroom by comparing select aspects of studying in both pre-and post-Bologna times at Salahaddin university-college of engineering. The methodology of this study is questionnaire-based cross-sectional survey of a random selection of architectural engineering students plus intensive interviews with experts in the field of architectural engineering. Regression analysis is applied to indicate the most operative factors among predictors (course factors, social factors and individual factors). Results specify that these factors have equivalent consequence on course selection and positively affected the students’ academic performance, in other hands the bologna process is one of the effective factors in improving Kurdistan higher education as comprehensive accreditation system.